Unity 2018 shaders and effects cookbook : transform your game into a visually stunning masterpiece with over 70 recipes - Doran, John P., 1988 or 1989-; Zucconi, Alan (Packt Publishing, 2018)
Bring realism to your games by mastering post-processing effects and advanced shading techniques in Unity 2018 About This Book Learn the secrets of creating AAA quality shaders without writing long algorithms Master shader programming through easy-to-follow examples Create stunning visual effects that can be used in 3D games Who This Book Is For Unity Shaders and Effects Cookbook is for developers who want to create their first shaders in Unity 2018 or wish to take their game to a whole new level by adding professional post-processing effects. A solid understanding of Unity is required to get the most from this book. What You Will Learn Understand physically based rendering to fit the aesthetic of your game Write shaders from scratch in ShaderLab and HLSL/Cg Combine shader programming with interactive scripts to add life to your materials Design efficient shaders for mobile platforms without sacrificing their realism Use state-of-the-art techniques, such as volumetric explosions and fur shading Master the math and algorithms behind the most used lighting models Understand how shader models have evolved and how you can create your own In Detail Since their introduction to Unity, shaders have been seen as notoriously difficult to understand and implement in games. Complex mathematics has always stood in the way of creating your own shaders and attaining the level of realism you crave. Unity 2018 Shaders and Effects Cookbook changes that by giving you a recipe-based guide to creating shaders using Unity. It will show you everything you need to know about vectors, how lighting is constructed with them, and how textures are used to create complex effects without the heavy math. This book starts by teaching you how to use shaders without writing code with the post-processing stack. Then, you'll learn how to write shaders from scratch, build up essential lighting, and finish by creating stunning screen effects just like those in high-quality 3D and mobile games. You'll discover techniques, such as normal mapping, image-based lighting, and animating your models inside a shader. We'll explore how to use physically based rendering to treat light the way it behaves in the real world. At the end, we'll even look at Unity 2018's new Shader Graph system. With this book, what seems like a dark art today will be second nature by tomorrow. Style and approach The recipes in this book contain step-by-step instructions, complemented with screenshots, code, and re ...